Deconstructing the Pilipino Values (Asia Pacific Journal of Social Innovation, 2022)
The prevailing narratives of the essence of the Pilipino values is very much leaning in the discourse of the Tagalog speakers. Hence, the Tagalog-termed concepts related to the values figure prominently in the literatures and textbooks that attempt to explain and impart the very core and ideals of being Pilipino. These are blindsided-linguistic perspectives anchored in the dominant Tagalog-based Filipino language, one among over-a-hundred languages spoken in the archipelago. A closer scrutiny into another dominant language, the Binisaya, reveals that there is a discrepancy in the reckoning of the values when analyzed and deconstructed linguistically. A discourse analysis shows similarities and differences of the usage of terminologies of the Pilipino values in spoken conversation. Similarities were taken as points of intersection of value practices showing coherence. Differences or the lack of counterpart terminologies will show divergence of values as practiced or analyzed in various literatures. This study argues that the Pilipino values, as gleaned from the discourse, reveals a superior-subordinate nexus that defines these values in the context of one’s power, position and status in the Philippine society. Further, this asserts that in order to imagine the Pilipino values in an inclusive context, the other languages must be included in the analysis, otherwise, the single-language lens becomes hegemonic, if not ethnocentric.